Cingulate cortex volumes in patients with bipolar disorder taking valproate versus valproate plus quetiapine - Atmaca, M.; Ozdemir, H.; Cetinkaya, S.; Parmaksiz, S.; Belli, H.; Poyraz, A. K.; Ogur, E. (Cambridge Univ Press, 2006)
[Abstract Not Available]
25th CINP Congress -- JUL 09-13, 2006 -- Chicago, IL